Cold cementation negative carbon aggregate prepared from steel slag and coal-based solid waste synergistically and preparation method of cold cementation negative carbon aggregate
Through the collaborative preparation and scientific process of steel slag and coal-based solid waste, the problem of difficulty in preparing carbon-negative aggregates with high strength and low water absorption in the existing technology has been solved, and the goals of resource utilization, energy conservation and environmental protection have been achieved.
Patent Information
- Application Number
- CN202411388641.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-17
AI Technical Summary
It is difficult for the prior art to effectively use steel slag and coal-based solid waste to prepare high-strength, low water absorption rate, and traditional sintering methods have problems of high energy consumption and high pollution.
By co-preparing steel slag and coal-based solid waste, using activators for pre-disintegration activation, combining grinding aids for ultra-fine grinding, adding pore-forming agents to generate microporous structures, and carbonizing through CO2 curing, the cold Cemented carbon negative aggregate.
It realizes the resource utilization of steel slag and coal-based solid waste, produces carbon-negative aggregate with high strength and low water absorption, avoids the high energy consumption and high pollution of traditional sintering methods, and achieves the purpose of energy conservation and environmental protection.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of resource utilization of solid waste, and in particular relates to a cold-bonded negative carbon aggregate prepared by synergistically using steel slag and coal-based solid waste, and a preparation method thereof. Background Art
[0002] Steel slag is the waste residue produced by removing impurities such as carbon, silicon, sulfur, phosphorus, and manganese from molten steel at a high temperature of more than 1600℃ during the steelmaking process in steel mills, including various oxides oxidized in molten steel, slag-making materials (silica, fluorite, dolomite, limestone, etc.), impurities brought in by furnace protection materials (magnesium oxide, etc.), corroded furnace body materials and lining materials, and alloy materials added to adjust the properties of steel. Steel slag is a by-product of steelmaking, accounting for 15-20% of crude steel production.
[0003] my country is the world's largest coal producer and consumer. With the mining, processing and utilization of coal, a large amount of coal-based solid waste is generated, such as coal gangue, fly ash, gasification slag, kaolin, etc. Coal gangue is mainly produced in the process of coal mining and washing. As of 2016, the cumulative stockpile of coal gangue in China has exceeded 7 billion tons, and with the continuous mining and processing of coal, its production is still increasing at a rate of 650 million to 750 million tons per year; coal gasification slag is the solid waste generated in the coal gasification process. At present, my country produces about 30 million tons of gasification slag each year. The treatment method of gasification slag is mainly storage and landfill, and large-scale comprehensive utilization has not yet been achieved. The amount of coal-based solid waste generated has always been large, but the disposal capacity is limited, and the problems it faces are becoming increasingly severe.
[0004] There is an urgent need to find a more environmentally friendly way to produce artificial aggregates instead of natural aggregates, as about three-quarters of the volume of concrete is occupied by aggregates. In recent years, the use of solid waste to prepare aggregates has attracted increasing attention. At present, how to use the synergistic effect between steel slag and coal-based solid waste as a method to prepare high-strength, low-water absorption, negative carbon aggregates has yet to be studied and developed. Summary of the invention
[0005] The purpose of the present invention is to propose a cold-bonded negative carbon aggregate prepared in collaboration with steel slag and coal-based solid waste and a preparation method thereof, to transform steel slag and coal-based solid waste into negative carbon lightweight aggregates, to utilize the chemical composition complementarity mechanism between various solid wastes, to achieve significant improvement in mechanical properties through scientific formula design and process route optimization, and to produce artificial lightweight aggregates with high strength and low water absorption and excellent performance.
[0006] In order to achieve the above purpose, this application adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a cold-cemented negative carbon aggregate prepared by synergistically preparing steel slag and coal-based solid waste, wherein the cold-cemented negative carbon aggregate comprises steel slag, coal-based solid waste, an activator, a grinding aid and a pore-forming agent.
[0008] In the above technical solution, the cold-bonded negative carbon aggregate is composed of the following raw materials in parts by mass: 20-50 parts of steel slag powder, 20-50 parts of coal-based solid waste, 1-5 parts of activator, 0.5-2.5 parts of grinding aid and 0-10 parts of pore former.
[0009] In the above technical scheme, the cylinder compressive strength of cold-bonded negative carbon aggregate is 13-28MPa, the water absorption rate is 9%-24%, and the bulk density is 700-1320kg / m 3 .
[0010] In the above technical solution, the coal-based solid waste includes one or more combinations of fly ash, gasified slag, coal gangue, and kaolin.
[0011] In the above technical solution, the activator includes a mixture of one or more of phosphoric acid, sodium sulfate, sodium silicate and sodium hydroxide.
[0012] In the above technical solution, the grinding aid includes a mixture of one or more of triethanolamine, amide, propylene glycol, maleic anhydride and acrylic acid.
[0013] In the above technical solution, the pore-forming agent includes one or more combinations of silicate microspheres, urea, aluminum powder, and expansion agent.
[0014] In a second aspect, the present invention provides a method for preparing the above-mentioned cold-cemented negative carbon aggregate, comprising the following steps:
[0015] S1: Mix the steel slag and the activator, put them into a ball mill and grind them to obtain activated steel slag;
[0016] S2: uniformly mixing the activated steel slag and the grinding aid, placing them in an ultrafine grinding machine for ultrafine grinding, and sieving them after grinding to obtain ultrafine modified steel slag powder;
[0017] S3: uniformly mix the coal-based solid waste and the activator, put them into a ball mill for ball milling, and sieve them after ball milling to obtain modified coal-based solid waste powder;
[0018] S4: uniformly mixing the ultrafine modified steel slag powder and modified coal-based solid waste powder obtained in S2 and S3 to obtain a batch material;
[0019] S5: uniformly mixing the batch material obtained in S4 with a pore-forming agent to obtain an aggregate raw material;
[0020] S6: The aggregate raw material obtained in S5 is granulated, left to stand, and carbonized and cured to obtain the cold-cemented negative carbon aggregate.
[0021] In the above technical solution, in S2, the specific surface area of the ultrafine modified steel slag powder is 350-500m 2 / g.
[0022] In S3, the sieving is through a 0.25 mm sieve.
[0023] In S6, the granulation method is as follows: the raw aggregate is put into a disc granulator, the disc angle is set to 40°-50°, and the rotation speed is 15rpm-20rpm. During the granulation process, water is sprayed to maintain the moisture content at about 25%, and the granulation process is completed within 15 minutes. The prepared spherical particles meet the particle classification requirements in GB / T 17461.1-2010.
[0024] In S6, the standing process is: after the granulation is completed, the spherical particles are kept at a temperature of 20-60° C. and a relative humidity of 40-60% for 24 hours.
[0025] In S6, the carbonization curing process is: the spherical particles obtained after granulation and standing are placed in a carbonization box with a temperature of 60±2°C, a relative humidity of 80±5%, and a CO2 concentration of 20-100% for carbonization for 12-24 hours to obtain the cold-bonded negative carbon aggregate.
[0026] The beneficial effects of the present invention are:
[0027] (1) The present invention uses an activator to pre-disintegrate and activate steel slag and coal-based solid waste, so as to break some chemical bonds in the steel slag and coal-based solid waste, which is beneficial for subsequent further grinding and bonding; then, a grinding aid is used to ultrafinely grind the steel slag, and the steel slag is micronized to obtain ultrafine steel slag powder.
[0028] (2) In the present invention, pore-forming agents such as silicate microspheres and aluminum powder are added to generate micropores inside the aggregate. The micropores have adsorption properties and adsorb CO2 during the carbonization process. CO2 can undergo carbonization reaction deep inside the aggregate, thereby improving the carbonization efficiency and enhancing the strength of the aggregate.
[0029] (3) The present invention uses CO2 to cure steel slag and coal-based solid waste artificial aggregates to further improve the strength of the aggregates, avoid the high energy consumption and high pollution caused by traditional sintering methods, save energy and fix CO2 to achieve carbon collection and storage effects.
[0030] (4) The present invention effectively utilizes steel slag and coal-based solid waste, thereby avoiding the high energy consumption and high pollution caused by traditional sintering methods, solving the pollution problem of the release of pollutants such as heavy metals, solid particles, etc. from steel slag and coal-based solid waste, and can turn waste into treasure and harm into benefit, thereby achieving the purpose of energy conservation and environmental protection, and alleviating the over-exploitation of natural aggregate resources in the building materials industry.
[0031] (5) The cold-bonded negative carbon aggregate of the present invention is lightweight and high-strength, has a simple preparation process, is suitable for industrial promotion and application, can be used as a lightweight building aggregate or building sand and gravel, and has excellent environmental, economic and social benefits. DETAILED DESCRIPTION
[0032] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. The present invention can be implemented in many different forms and should not be construed as being limited to the embodiments set forth herein. On the contrary, these embodiments are provided so that this disclosure will be thorough and complete, and the concept of the present invention will be fully conveyed to those skilled in the art, and the present invention will only be limited by the claims.
[0033] Example 1
[0034] A cold-bonded negative carbon aggregate prepared by synergistically using steel slag and coal-based solid waste, and the preparation method thereof is as follows:
[0035] 40 parts of steel slag and 3 parts of sodium sulfate are mixed evenly, put into a ball mill for ball milling, and activated steel slag is obtained; then the activated steel slag and 1 part of triethanolamine are mixed evenly, put into an ultrafine grinding machine for ultrafine grinding, and sieved after grinding to obtain ultrafine modified steel slag powder; 30 parts of gasified slag, 30 parts of coal gangue and 3 parts of sodium sulfate are mixed evenly, put into a ball mill for ball milling, and sieved after ball milling to obtain modified coal-based solid waste powder;
[0036] 40 parts of steel slag, 30 parts of gasified slag and 30 parts of coal gangue are mixed evenly and put into a disc granulator for granulation. During the granulation process, water is sprayed to keep the moisture content at about 25%. The granulation process is completed within 15 minutes. The obtained fresh pellets are kept at a temperature of 20°C and a relative humidity of 40-60% for 24 hours to obtain raw pellets.
[0037] The raw material balls are placed in a carbonization box at a temperature of 60±2°C, a relative humidity of 80±5%, and a CO2 concentration of 20-100% for carbonization for 24 hours to obtain cold-bonded negative carbon aggregate.
[0038] Example 1 has a bulk density of about 903.6 kg / m 3 The artificial lightweight aggregate has a water absorption rate of 12.4% in 1h and a cylinder compressive strength of 13.9MPa.
[0039] Example 2
[0040] A cold-bonded negative carbon aggregate prepared by synergistically using steel slag and coal-based solid waste, and the preparation method thereof is as follows:
[0041] 50 parts of steel slag and 5 parts of sodium hydroxide are mixed evenly, and the mixture is put into a ball mill for ball milling to obtain activated steel slag; the activated steel slag and 0.5 parts of propylene glycol are mixed evenly, and the mixture is put into an ultrafine grinding machine for ultrafine grinding, and the ultrafine modified steel slag powder is obtained by sieving after grinding; 20 parts of gasified slag, 10 parts of coal gangue, 20 parts of kaolin and 5 parts of sodium hydroxide are mixed evenly, and the mixture is put into a ball mill for ball milling, and the modified coal-based solid waste powder is obtained by sieving after ball milling;
[0042] 50 parts of steel slag, 20 parts of gasified slag, 10 parts of coal gangue, 20 parts of kaolin and 3 parts of silicate microspheres were mixed evenly and put into a disc granulator for granulation. During the granulation process, water was sprayed to keep the moisture content at about 25%. The granulation process was completed within 15 minutes. The obtained fresh material balls were kept at a temperature of 20°C and a relative humidity of 40-60% for 24 hours to obtain raw material balls.
[0043] The raw material balls are placed in a carbonization box at a temperature of 60±2°C, a relative humidity of 80±5%, and a CO2 concentration of 20-100% for carbonization for 24 hours to obtain cold-bonded negative carbon aggregate.
[0044] Example 2: The bulk density is about 1050.3 kg / m 3 The artificial lightweight aggregate has a water absorption rate of 15.6% in 1h and a cylinder compressive strength of 16.5MPa.
[0045] Example 3
[0046] A cold-bonded negative carbon aggregate prepared by synergistically using steel slag and coal-based solid waste, and the preparation method thereof is as follows:
[0047] 30 parts of steel slag and 5 parts of sodium silicate are mixed evenly, put into a ball mill and milled to obtain activated steel slag; then the activated steel slag and 1 part of maleic anhydride are mixed evenly, put into an ultrafine grinding machine for ultrafine grinding, and sieved after grinding to obtain ultrafine modified steel slag powder; 30 parts of fly ash, 20 parts of coal gangue, 20 parts of kaolin and 5 parts of sodium silicate are mixed evenly, put into a ball mill and milled, and sieved after ball milling to obtain modified coal-based solid waste powder;
[0048] 30 parts of steel slag, 30 parts of fly ash, 20 parts of coal gangue, 20 parts of kaolin and 2 parts of aluminum powder were mixed evenly and put into a disc granulator for granulation. During the granulation process, water was sprayed to keep the moisture content at about 25%. The granulation process was completed within 15 minutes. The obtained fresh material balls were kept at a temperature of 20°C and a relative humidity of 40-60% for 24 hours to obtain raw material balls.
[0049] The raw material balls are placed in a carbonization box at a temperature of 60±2°C, a relative humidity of 80±5%, and a CO2 concentration of 20-100% for carbonization for 24 hours to obtain cold-bonded negative carbon aggregate.
[0050] Example 3 has a bulk density of about 741.4 kg / m 3 The artificial lightweight aggregate has a water absorption rate of 13.2% in 1h and a cylinder compressive strength of 18.8MPa.
[0051] Example 4
[0052] A cold-bonded negative carbon aggregate prepared by synergistically using steel slag and coal-based solid waste, and the preparation method thereof is as follows:
[0053] 30 parts of steel slag, 2.5 parts of sodium silicate and 2.5 parts of sodium hydroxide are mixed evenly, and the mixture is put into a ball mill for ball milling to obtain activated steel slag; the activated steel slag and 1 part of maleic anhydride are mixed evenly, and the mixture is put into an ultrafine grinding machine for ultrafine grinding, and the ultrafine modified steel slag powder is obtained by sieving after grinding; 30 parts of fly ash, 20 parts of coal gangue, 20 parts of kaolin, 2.5 parts of sodium silicate and 2.5 parts of sodium hydroxide are mixed evenly, and the mixture is put into a ball mill for ball milling, and the modified coal-based solid waste powder is obtained by sieving after ball milling;
[0054] 30 parts of steel slag, 30 parts of fly ash, 20 parts of coal gangue, 20 parts of kaolin and 2 parts of aluminum powder were mixed evenly and put into a disc granulator for granulation. During the granulation process, water was sprayed to keep the moisture content at about 25%. The granulation process was completed within 15 minutes. The obtained fresh material balls were kept at a temperature of 20°C and a relative humidity of 40-60% for 24 hours to obtain raw material balls.
[0055] The raw material balls are placed in a carbonization box at a temperature of 60±2°C, a relative humidity of 80±5%, and a CO2 concentration of 20-100% for carbonization for 24 hours to obtain cold-bonded negative carbon aggregate.
[0056] Example 4 has a bulk density of about 746.3 kg / m 3 The artificial lightweight aggregate has a water absorption rate of 12.4% in 1h and a cylinder compressive strength of 27.6MPa.
[0057] Example 5
[0058] A cold-bonded negative carbon aggregate prepared by synergistically using steel slag and coal-based solid waste, and the preparation method thereof is as follows:
[0059] 20 parts of steel slag and 5 parts of sodium silicate are mixed evenly, put into a ball mill and milled to obtain activated steel slag; then the activated steel slag and 1 part of amide are mixed evenly, put into an ultrafine grinding machine for ultrafine grinding, and sieved after grinding to obtain ultrafine modified steel slag powder; 30 parts of fly ash, 20 parts of coal gangue, 30 parts of kaolin and 5 parts of sodium silicate are mixed evenly, put into a ball mill and milled, and sieved after ball milling to obtain modified coal-based solid waste powder;
[0060] 20 parts of steel slag, 30 parts of fly ash, 20 parts of coal gangue, 30 parts of kaolin and 2 parts of urea are mixed evenly and put into a disc granulator for granulation. During the granulation process, water is sprayed to keep the moisture content at about 25%. The granulation process is completed within 15 minutes. The obtained fresh material balls are kept at a temperature of 20°C and a relative humidity of 40-60% for 24 hours to obtain raw material balls.
[0061] The raw material balls are placed in a carbonization box at a temperature of 60±2°C, a relative humidity of 80±5%, and a CO2 concentration of 20-100% for carbonization for 24 hours to obtain cold-bonded negative carbon aggregate.
[0062] Example 5: The bulk density is about 707.1 kg / m 3 The artificial lightweight aggregate has a water absorption rate of 10.6% in 1h and a cylinder compressive strength of 15.2MPa.
[0063] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A cold-cemented negative carbon aggregate prepared by synergistically using steel slag and coal-based solid waste, characterized in that: The cold-bonded negative carbon aggregate comprises steel slag, coal-based solid waste, an activator, a grinding aid and a pore-forming agent.
2. The cold-bonded negative carbon aggregate according to claim 1, characterized in that: The cold-bonded negative carbon aggregate is composed of the following raw materials in parts by mass: 20-50 parts of steel slag powder, 20-50 parts of coal-based solid waste, 1-5 parts of activator, 0.5-2.5 parts of grinding aid and 0-10 parts of pore former.
3. The cold-bonded negative carbon aggregate according to claim 1, characterized in that: The cylinder compressive strength of cold-bonded negative carbon aggregate is 13-28MPa, the water absorption rate is 9%-24%, and the bulk density is 700-1320kg / m 3 .
4. The cold-bonded negative carbon aggregate according to claim 1, characterized in that: The coal-based solid waste includes one or more combinations of fly ash, gasified slag, coal gangue and kaolin.
5. The cold-bonded negative carbon aggregate according to claim 1, characterized in that: The activator comprises a mixture of one or more of phosphoric acid, sodium sulfate, sodium silicate and sodium hydroxide.
6. The cold-bonded negative carbon aggregate according to claim 1, characterized in that: The grinding aid comprises a mixture of one or more of triethanolamine, amide, propylene glycol, maleic anhydride and acrylic acid.
7. The cold-bonded negative carbon aggregate according to claim 1, characterized in that: The pore-forming agent includes one or more combinations of silicate microspheres, urea, aluminum powder, and expansion agents.
8. The method for preparing the cold-cemented negative carbon aggregate according to any one of claims 1 to 7, characterized in that: The steps include: S1: Mix the steel slag and the activator, put them into a ball mill and grind them to obtain activated steel slag; S2: uniformly mixing the activated steel slag and the grinding aid, placing them in an ultrafine grinding machine for ultrafine grinding, and sieving them after grinding to obtain ultrafine modified steel slag powder; S3: uniformly mix the coal-based solid waste and the activator, put them into a ball mill for ball milling, and sieve them after ball milling to obtain modified coal-based solid waste powder; S4: uniformly mixing the ultrafine modified steel slag powder and modified coal-based solid waste powder obtained in S2 and S3 to obtain a batch material; S5: uniformly mixing the batch material obtained in S4 with a pore-forming agent to obtain raw aggregate; S6: The aggregate raw material obtained in S5 is granulated, left to stand, and carbonized and cured to obtain the cold-cemented negative carbon aggregate.
9. The preparation method according to claim 8, characterized in that: In S2, the specific surface area of the ultrafine modified steel slag powder is 350-500m 2 / g.
10. The preparation method according to claim 8, characterized in that: In S6, the carbonization curing process is: the spherical particles obtained after granulation and standing are placed in a carbonization box with a temperature of 60±2°C, a relative humidity of 80±5%, and a CO2 concentration of 20-100% for carbonization for 12-24 hours to obtain the cold-bonded negative carbon aggregate.
Citation Information
Cited By
Method for preparing mine negative carbon filling material based on solid waste-based carbonized aggregate
CN120136468A
Ecological carbon sequestration aggregate based on coal mine slag powder and preparation method of ecological carbon sequestration aggregate
CN121573925A
All-solid-waste two-stage carbon sequestration alkali-activated geopolymer concrete and preparation method thereof
CN122325160A